CHALLENGES AND STRATEGIES IN INTEGRATING SOCIAL DETERMINANTS OF HEALTH DATA INTO COMPREHENSIVE MEDICAL RECORDS - Fatmah Mousa Joubran Mueeni, Muneef Dhahawi Al Enazi, May Saeed Alymi, Nasser Abdullah Aldossari, Saeed Ali Alamri, Abdullah Turki Aloraini, Ali Geza Gazi Almutairi, Sattam Awad Khwaishan Almutairi, Majed Gabul Mgbal Almotairi, ,; Fares Abdulaziz Sharid Al-mutairi, Sttam Bandar Jaiez Almetairy, Mishari Fuhaid Mohammed Al-mutairi, Khadijah Ahmad Abdallh Bin Zarah, Munif Menwer Alruwaili, Majed Mohammed Aldabaan, (Chelonian Research Foundation, 2022)
With the increasing emphasis on population health in healthcare, healthcare practitioners are recognizing that data beyond conventional clinical results may provide a more comprehensive understanding of the factors influencing a patient's health condition. This data can also help discover strategies to enhance the efficacy of therapy. Nevertheless, there are still other obstacles that need to be overcome in order to make data pertaining to social aspects of health, such as living circumstances and levels of education, as accessible and usable as medical data. The main obstacles include the absence of agreement on standards for recording or indicating social variables of health in electronic health records, as well as a lack of evidence demonstrating the effectiveness of addressing social determinants through referrals or other action tools once the information has been collected. In order to tackle these difficulties and efficiently utilize social determinants in healthcare environments, we propose the establishment of nationwide guidelines for representing data pertaining to social determinants of health in electronic health records. Additionally, we suggest providing incentives, either financial or based on quality, to encourage the collection of such data. Furthermore, we recommend expanding the scope of research that assesses the consequences of acting upon the gathered information. Keywords: Social determinants, electronic health records, guidelines, review, strategies, challenges.